Near approximations via general ordered topological spaces (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we intdoduce near approximation via general ordered topological approximation spaces which may be viewed as a generalization of the study of near approximation from the topological view. The basic concepts of some increasing (decreasing) near approximations, increasing (decreasing) near boundary regions and increasing (decreasing) near accuracy were introduced and sufficiently illustrated. Moreover, proved results, implications and add examples.